Amelioration of Sarcoptic Mange-Induced Oxidative Stress and Apoptosis in Dogs by Using Calendula officinalis Flower Extracts. (30th October 2013) - Singh, Shanker K.; Dimri, Umesh
Abstract : Twenty-four clinically Sarcoptes -infested dogs were randomly enrolled into three groups (groups A, B, and C), 8 dogs in each group. Group A was treated with ivermectin + Calendula officinalis flower extract (CFE). Group B was treated with ivermectin + N-acetyl cysteine (NAC) (standard positive controls), while group C (negative control) was treated with ivermectin alone. Another eight healthy dogs were used as healthy controls (group D). By day 28 after therapy, the dogs treated adjunctly with CFE as well as with N-acetyl cysteine revealed significant (P ≤ 0.001 ) amelioration of the altered markers of oxidative stress towards normalcy. The dogs of these groups also revealed significant (P ≤ 0.001 ) amelioration of apoptotic leukocytes towards normalcy, and values were comparable to those of the healthy controls. While by day 28 after therapy, ivermectin alone treated dogs could not achieve comparable values to those of the healthy controls. The dogs treated adjunctly with CFE and N-acetyl cysteine also revealed faster parasitological as well as clinical cure rate as compared to the ivermectin alone treated dogs. In conclusion, CFE has remarkable antioxidant and antiapoptotic potential and can constitute a potential adjunctive remedy with miticide for the therapeutic management of canine sarcoptic mange.